Review of reported adverse drug reactions in a local health facility. (10th June 2015) - Ierano, Courtney; Morrissey, Hana; Ball, Patrick; Nielsen, Sharon
Abstract: Background: Adverse drug reactions (ADRs) are common, causing significant morbidity and mortality. In 2011, there were approximately 247 000 reports of suspected ADRs reported to the Australian Therapeutics Goods Administration. It has been reported that in 2003, 2–4% of all hospital admissions were medication‐related, and up to 75% of these were thought to be potentially preventable, costing the health system approximately 400 million. Aim: To review the ADRs reported in a rural hospital and estimate the proportion that could have been predicted and/or prevented so as to inform future prevention strategies. Method: This was a retrospective observational study conducted in a rural hospital in Australia. The study involved systematic review of the cases of patients admitted during a 1‐month period. The prevalence of ADRs, the clinical history, the causative agent and the type of reaction were recorded. The preventability, predictability and severity of the ADRs were evaluated using validated instruments. Results: There were 735 patients admitted to hospital during the data collection period, and the cases of 200 renal dialysis patients were excluded from further analysis on the basis of the atypical pattern of admissions for this group. Data from the remaining 535 patients were reviewed, and in 118 cases, these did not have a National Inpatient Medication Chart as they were admitted to the emergency department or day surgery unit. In total, 417 National Inpatient Medication Charts were available for further analysis. There were recorded ADRs in 90 cases, and on some charts multiple ADRs were recorded. A total of 150 recorded ADRs were investigated, and ultimately 82% were considered to have been predictable and 97% were considered to be preventable. Conclusion: This research suggests that ADRs are often both predictable and preventable. Further measures need to be implemented to ensure correct recording of ADRs, to inform appropriate patient management and to minimise associated harm and optimise health outcomes.